Accuracy of closed-loop and open-loop propofol delivery systems by bispectral index monitoring in breast surgery patients: a prospective randomized trial - Tian Xie; Yong Wang; Yuhua Liu; Junjie Li; Weijing Li; Hongmeng Xu (Brazilian Journal of Anesthesiology, 2024)
Background: This randomized and controlled prospective study tested the hypothesis that closed-loop Target-Controlled Infusion (TCI) of propofol would be associated with better system performance when compared with open-loop controlled delivery of propofol. Methods: Patients scheduled for elective breast surgery were randomly assigned to two groups: a closed-loop group, in which propofol infusion was performed by a closed-loop TCI system that used the Bispectral Index (BIS) as a feedback parameter to titrate the rate of propofol infusion, and an open-loop group, in which propofol infusion was performed manually and guided by the bispectral index. Results: A total of 156 patients were recruited for this study (closed-loop group n = 79; open-loop group n = 77). The Global Score (GS) of the closed-loop group was lower than that of the open-loop group (34.3 and 42.2) (p = 0.044). The proportions of time with a BIS value between 40 and 60 were almost identical in the closed-loop group and the open-loop group (68.7 ± 10.6% and 66.7 ± 13.3%) (p = 0.318). The individuals in the closed-loop group consumed more propofol compared with those in the open-loop group (7.20 ± 1.65 mg.kg−1.h−1 vs. 6.03 ± 1.31 mg.kg−1.h−1, p < 0.001). No intraoperative recall, somatic events or adverse events occurred. No significant difference in heart rate was observed between the two groups (p = 0.169). Conclusion: The closed-loop protocol was associated with lower BIS variability and lower out-of-range BIS values, at the cost of a greater consumption of propofol when compared to the open loop group. Register number: ChiCTR-INR-17010399.